The answer for the above problem is found to be "(x+6)X(x-2)"
Explanation:
+ 4x - 12
= x^2 + 4x + 4 - 4 - 12
=x^2+ 4x + 4 - 16
=(x+2)^2 - 4^2
=(x+2+4)X(x+2-4)
=(x+6)X(x-2)
here is the explanations
since we have x^2, so we try to write the equation in (a+b)^2 = a^2 + 2ab + b^2 form.
to make it in square form we add 4 ( see at the second line). now we took 4 extra so we subtract 4 again.
in third line we have now x^2 + 4x + 4, this is perfect square in the form of (x+4)^2. next we took 16 as 4^2
in fourth line we apply (a+b)X(a-b) = a^2 - b^2 formula. here we took a = (x+4) and b= 4
then finally we get the answer as (x+6)X(x-2)